Efeito citotóxico de um derivado sintético do INDOL em linhagem de melanoma e carcinoma de pulmão - Bonifacio, João Henrique Oliveira (2024)
Cancer is a multifactorial disease characterized by disordered cell division. Cancer treatments is often nonspecific and highly cytotoxic, affecting also nontumor cells. In the search for new antineoplastic compounds, research into derivatives of natural products has proved increasingly promising and reveals the constant evolution of science to provide treatments with fewer adverse effects. Indole is a natural compound found in plants and microorganisms with proven anti-tumor activity. Modifications to its structure can potentiate its cytotoxic action on tumor cells. The aim of this study was to evaluate the cytotoxic potential of the synthetic indole derivative 1-(1-tosyl-1H-indol- 3-yl)propan-1-one in tumor cell lines. For this, sulforhodamine B (SRB) was used to determine the cytotoxic effect of compound 1-(1-tosyl-1H-indol-3-yl)propan-1-one in melanoma (B16F10), lung cancer (A549), breast cancer (MCF7) and prostate cancer (PC-3) cell lines. In vitro clonogenic and cell migration assays were carried out to analyze the colony formation and migratory capacity of the A549 and B16F10 cell lines. DAPI and Phalloidin/FITC were used to observe morphological changes in the A549 and B16F10 cell lines after the treatment with compound 1-(1-tosyl-1H-indol-3- yl)propan-1-one. The type of cell death was analyzed by flow cytometry and then the hemolysis assay was performed on human and C57BL/6 mouse erythrocytes. All the tests were carried out in three independent experiments and the results were represented as means and 95% confidence intervals. ANOVA followed by Dunnett's post-test was used to analyze comparisons between groups. Values of p<0.05 were considered statistically significant. As a result, we observed a high inhibition of cell growth with IC50 less than or equal to 10 μM in the four cell lines studied. The greatest inhibition effects were observed in the A549 and B16F10 cell lines with IC50 of 2.6 and 7.6 μM, respectively. The A549 and B16F10 cell lines were selected for the next biological tests considering the IC50 and the epidemiological relevance of these cancers. In the colony formation assay, clone inhibition was observed in the A549 cell line at a concentration of 5.2 μM and in the B16F10 cell line at concentrations of 3.8 to 15.2 μM. In the migration analysis, we observed that the compound inhibited the closure of the stripe in the A549 and B16F10 cell lines at the highest concentrations after 48 hours of treatment. In addition, morphological changes characteristic of apoptosis were observed in the A549 and B16F10 cell lines by DAPI and Phalloidin/FITC labeling, such as cytoplasmic reduction and changes in the arrangement of actin filaments. These results corroborate flow cytometry, which showed that the treatment induced apoptosis in the A549 and B16F10 cell lines. No hemolytic activity was observed in human erythrocytes and C57BL/6 mouse after exposure to the compound. Our results show that treatment with compound 1-(1-tosyl- 1H-indol-3-yl)propan-1-one in A549 and B16F10 cell lines inhibited cell growth and migration, as well as inducing cell death by apoptosis.